Hierarki Kebutuhan Tokoh Takamiya Naho dalam Anime Orange: Kajian Psikologi Humanistik Abraham Maslow - Zaufa, Syahkila; Oemiati, Sri (Vocational College of Diponegoro University, 2025)
This study is based on the phenomenon in the anime Orange, which depicts the psychological dynamics of the main character, Naho Takamiya, in facing life challenges and interpersonal relationships. The issue raised in this study is how Abraham Maslow's hierarchy of needs is reflected through the behaviour and dialogue of the character. This study aims to describe Abraham Maslow's humanistic psychology theory in the anime Orange. The method used is qualitative descriptive with data collection techniques conducted through observation and documentation. The data analysed consists of dialogues related to Abraham Maslow's hierarchy of needs. The results show that Naho Takamiya fulfils all five levels of needs according to Maslow’s theory: physiological needs, safety needs, love and belonging needs, esteem needs, and self-actualisation needs. This study shows that character development in fictional works can be analysed through a psychological perspective.